2022
DOI: 10.3390/ani12243473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Stress on Thermoregulation, Hematological and Hormonal Characteristics of Caracu Beef Cattle

Abstract: This study evaluated the influence of environmental temperature on thermoregulation, hormonal, and hematological characteristics in Caracu cattle. Blood samples, hair length, coat and muzzle colors, rectal (RT), and surface temperatures were collected from 48 males and 43 females before (morning) and after sun exposure for eight hours (afternoon). Infrared thermography (IRT) was used to identify superficial temperature that exhibits a high correlation with RT. Hematological parameters, hormone concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 66 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…According to [16,43], RBC and Ht decrease with heat stress; therefore, there was no such effect in the evaluated breed groups. Except for SE, which presented mean results lower than the others, however, this cannot be considered only as a temperature effect.…”
Section: Discussionmentioning
confidence: 85%
“…According to [16,43], RBC and Ht decrease with heat stress; therefore, there was no such effect in the evaluated breed groups. Except for SE, which presented mean results lower than the others, however, this cannot be considered only as a temperature effect.…”
Section: Discussionmentioning
confidence: 85%
“…The decrease in the erythrocytic count in polled Bali cattle indicates that sun exposure and exercise during the day can interfere with erythrocytes, as explained by Tamzil et al (2014) that heat stress can affect the erythropoietin hormone in the spinal cord so that the production and development of erythrocytes are inhibited. Abduch et al (2022) reported that daytime sun exposure and exercise had a negative impact on the number of erythrocytes in Caracu beef cattle. Ondruska et al (2011) also reported that rabbits exposed to 36°C daily, for 12 h, within 4 weeks were able to reduce the erythrocytic count.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Animal thermoregulation is a set of mechanisms that seek to adjust the internal body temperature of animals, in an attempt to maintain it at values compatible with life, when there is fluctuation in the temperature of the environment [ 1 , 2 ]. The use of these mechanisms has a direct influence on the animal’s behavior, energy expenditure and performance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%